2018
DOI: 10.1016/j.celrep.2018.11.036
|View full text |Cite
|
Sign up to set email alerts
|

The Dachsous/Fat/Four-Jointed Pathway Directs the Uniform Axial Orientation of Epithelial Cells in the Drosophila Abdomen

Abstract: Highlights d Histoblasts progressively align with the A/P axis of the abdominal epithelium d The uniform axial orientation of cell alignment requires the Ds/Ft/Fj pathway d Planar polarity of histoblasts is independent of the Ds/Ft/Fj pathway d Axially patterned Ds and Ft adhesive interactions guide orientation dynamics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 83 publications
4
29
0
Order By: Relevance
“…Cell polarization dictates the direction of growth and might be coordinately affected by forces from neighboring cells. During expansion, we have found that cell elongation affects the orientation of anisotropic growth (Mangione & Martin-Blanco, 2018). While we did not analyze/discriminate stress polarity in a radial configuration, we found that the final global polarization of the abdominal epidermis responds to the axial alignment of histoblast orientation.…”
Section: Mechanical Coupling Of Growth and Deathmentioning
confidence: 75%
See 3 more Smart Citations
“…Cell polarization dictates the direction of growth and might be coordinately affected by forces from neighboring cells. During expansion, we have found that cell elongation affects the orientation of anisotropic growth (Mangione & Martin-Blanco, 2018). While we did not analyze/discriminate stress polarity in a radial configuration, we found that the final global polarization of the abdominal epidermis responds to the axial alignment of histoblast orientation.…”
Section: Mechanical Coupling Of Growth and Deathmentioning
confidence: 75%
“…Myo-GFP transgenic pupae were used to visualize the cortex displacements. This constitutes an emerging property of the tissue, dictated by the activity of the Ft/Ds/Fj pathway, which define a patterned cell adhesiveness landscape (Mangione & Martin-Blanco, 2018). Scale bar = 15 lm.…”
Section: Of 15mentioning
confidence: 99%
See 2 more Smart Citations
“…They subsequently developed an elegant and minimal mechanical model for tissue dynamics that captures the essential physics of this morphogenetic process. Finally, Enrique Martin-Blanco (CSIC, Barcelona, Spain) discussed tissue replacement during metamorphosis, detailing the mechanical cell behaviours and molecular pathways that allow newly formed adult epithelial cells, generated by histoblasts, to invade and replace the larval epithelium (Ninov et al, 2007;Ninov et al, 2010;Mangione et al, 2018).…”
Section: Emergent Properties and Self-organization: From Molecules Tomentioning
confidence: 99%